Критериальная модель соотнесенности интенсивности семантического признака с количественным проявлением его акустических коррелятов - Могилевский, В.; Королева, Т. (Лексикографічний бюлетень, 2006)
The criteria model, moved forward in the article, reflects the correlation between the degree of semantic indicator being present in either member within the functional and semantic field ― "degree of responsibility" and acoustic characteristics of this indicator.